Investigating epigenetic loci implicated in Alzheimer's disease via the CRISPR‐Cas9 system. (1st February 2022) - Schrauben, Michael; Washer, Sam; Smith, Adam R.; Dempster, Emma; Lunnon, Katie
Abstract: Background: Differentially methylated positions (DMPs) identified by Epigenome‐wide association studies (EWAS) of Alzheimer's disease (AD) were modified by the CRISPR‐Cas9 system to investigate the role of epigenetic alterations in AD pathogenesis. Method: Cell lines of neuronal phenotype (SH‐SY5Y) and microglial phenotype (IHM‐SV40) were used to explore the functional consequence of loci demethylation, where removal of the methyl groups was achieved by the modified CRISPR‐dCas9 system. Lentiviral delivery of the dCas9‐TET1CD demethylase tool and guide RNA (gRNA) constructs targeting the CpG sites associated with differential expression of ANK1 and BIN1 in AD was validated by fluorescence activated cell sorting (FACS). Bisulphite pyrosequencing was applied to confirm the DNA methylation edit and RT‐qPCR was performed to assess changes in mRNA expression. Result: High transduction efficiencies were observed during FACS of SH‐SY5Y cells transduced with CRISPR‐dCas9 constructs targeting the BIN1 locus and IHM‐SV40 cells with constructs against the ANK1 locus. Methylation analysis of these target regions in the modified cell lines demonstrated a reduction in methylation when compared to the untreated control cells. Full‐length transcript expression levels of ANK1 and BIN1 showed no significant differences between experimental conditions. Conclusion: Delivery and activity of our CRISPR‐dCas9 fusion constructs was demonstrated in cell line models of AD.